Gel electrolyte and preparation method and application thereof

By using metal ion modified Nafion separators in aqueous batteries, the cycle stability and reversible capacity of the electrode material are enhanced, and the problems of poor cycle stability and low reversible capacity in the aqueous electrolyte in the prior art are solved, thereby achieving stable improvement of battery capacity and extending battery life.

CN119725716APending Publication Date: 2025-03-28BEIJING INST OF NANOENERGY & NANOSYST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510127815.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, organic electrode materials have poor circulation stability and low reversible capacity in aqueous electrolytes, resulting in a continuous decline in battery capacity, affecting the number of cycles and battery life.

Method used

The Nafion separator modified with metal ion is used to enhance the three-dimensional network structure of the Nafion membrane through the strong interaction between metal ions and sulfonic acid groups in Nafion, and gradually swell the gel network with an aqueous electrolyte to form a hydrophilic channel to improve the ionic conductivity.

Benefits of technology

Effectively suppress the dissolution and shuttle of organic electrode materials, improve the cycle stability and reversible capacity of the battery in the aqueous electrolyte, and extend the effective use period of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725716A_ABST
    Figure CN119725716A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage materials, and discloses a gel electrolyte and a preparation method and application thereof. The electrolyte comprises an electrolyte solution and a Nafion diaphragm modified by metal ions, wherein the metal ions are selected from at least one of IA group elements, IIA group elements and IIIA group elements; wherein on the basis of the total amount of the metal ion modified Nafion diaphragm, the content of the metal ions is 0.1-5 wt%. The electrolyte can improve the cycling stability and reversible capacity of the aqueous battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage materials, and in particular to a gel electrolyte and a preparation method and application thereof. Background Art

[0002] In order to balance the needs of energy conservation and emission reduction with economic development, electrochemical energy storage technologies with high convenience, no geographical restrictions, short construction period and high conversion efficiency have gradually become the focus of attention. Among them, lithium-ion batteries have always been in a leading position in the market share of high-end electronic products and electric vehicles with their excellent performance such as high energy density, high output power and long cycle life. However, due to the scarcity of cobalt, it is difficult to maintain large-scale sustainable production of lithium-ion batteries for a long time. And because of the use of flammable electrolytes and diaphragm materials, lithium-ion batteries are prone to fire or explosion after thermal runaway, thus posing a huge safety hazard. Correspondingly, aqueous batteries are safer and more environmentally friendly. Therefore, organic electrodes / aqueous batteries with high specific capacity and long cycle life will also become a strong competitor for large-scale energy storage devices in the future.

[0003] Traditionally, soluble organic electrode materials inevitably enter the electrolyte during the cycle and pass through the diaphragm to the counter electrode driven by diffusion and electric field, resulting in a continuous decrease in capacity until dissolution equilibrium. Therefore, inhibiting the dissolution and shuttling of organic electrode materials is crucial for the development of next-generation aqueous batteries. Hydrogel electrolytes have gradually attracted attention in aqueous battery research due to their excellent ion conductivity and mechanical durability. Its aqueous electrolyte and porous gel skeleton structure avoid electrolyte leakage and the use of diaphragms. In addition, due to the reduction of free water in the hydrogel, the activity of water molecules is also reduced, thereby minimizing the occurrence of side reactions and improving the cycle stability of the battery.

[0004] Nafion, as a sulfonate-containing perfluoropolymer, has excellent mechanical and chemical stability. In addition, the hydration of the sulfonic acid group enhances the proton transport capacity of Nafion, making it widely used as a proton transport membrane in aqueous fuel cells and flow batteries. Reported modification technologies include CN111525167B and CN115312972B, which respectively improve the cycle stability of aqueous vanadium-based flow batteries and organic lithium flow batteries through Nafion composite separation membranes. The disadvantage is that due to the strong hydrophobicity of the perfluoropolymer chain, the Nafion membrane is difficult to be swollen by water to form a stable hydrophilic proton transport channel, so that it is impossible to obtain an ideal and stable ionic conductivity, which limits its application in hydrogel electrolytes. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor cycle stability and low reversible capacity of organic electrode materials in aqueous electrolytes in the prior art, and to provide a gel electrolyte and a preparation method and application thereof to improve the cycle stability and reversible capacity of aqueous batteries.

[0006] In order to achieve the above object, the present invention provides a gel electrolyte in a first aspect, wherein the electrolyte comprises an electrolyte solution and a Nafion membrane modified by metal ions;

[0007] Wherein, the metal ion is selected from at least one of Group IA, Group IIA and Group IIIA elements;

[0008] Wherein, based on the total amount of the metal ion-modified Nafion membrane, the content of the metal ions is 0.1-5% by weight.

[0009] Preferably, the metal ion is selected from at least one of barium ion, aluminum ion, magnesium ion and calcium ion.

[0010] A second aspect of the present invention provides a method for preparing a gel electrolyte, wherein the method comprises the following steps:

[0011] (1) preparing a solution containing a first solvent and Nafion-H, and then performing a membrane forming process to obtain a Nafion-H membrane;

[0012] (2) in the presence of a second solvent, bringing the Nafion-H membrane into first contact with a metal precursor to obtain a metal ion-modified Nafion membrane;

[0013] Wherein, the metal in the metal precursor is selected from at least one of Group IA, Group IIA and Group IIIA elements;

[0014] The amount of Nafion-H membrane and metal precursor used is such that the metal ion content in the prepared metal ion-modified Nafion membrane is 0.1-5 wt %;

[0015] (3) in the presence of an organic solvent, the metal ion-modified Nafion membrane contacts the first electrolyte and swells;

[0016] (4) contacting the product obtained in step (3) with a second electrolyte to replace the organic solvent.

[0017] The third aspect of the present invention provides a gel electrolyte prepared by the method described in the second aspect.

[0018] The fourth aspect of the present invention provides use of the gel electrolyte described in the first aspect and the third aspect in a battery.

[0019] Through the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) In the prior art, organic electrode materials are easily dissolved and shuttled to the counter electrode during the circulation of aqueous electrolytes, resulting in a continuous decrease in capacity, which seriously affects the number of cycles and overall life of the battery. The gel electrolyte of the present invention, with the help of the metal ion-modified Nafion diaphragm, can effectively inhibit the dissolution and shuttle of organic electrode materials, thereby improving the cycle stability of the battery in the aqueous electrolyte, greatly extending the effective service life of the battery, and better meeting the needs of long-term stable operation of large-scale energy storage equipment.

[0021] (2) The gel electrolyte provided by the present invention optimizes the interface environment between the electrode and the electrolyte, reduces the occurrence of side reactions, is more conducive to the reversible reaction of the electrode material during the charge and discharge process, and improves the reversible capacity of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The acidic Nafion-Ba in Example 1 2+ Appearance of hydrogel electrolyte;

[0023] Figure 2 This is a half-battery cycle performance test diagram in Example 1;

[0024] Figure 3 This is a half-cell cycle performance test diagram in Example 2;

[0025] Figure 4 This is a half-cell cycle performance test diagram in Example 3;

[0026] Figure 5 This is a full battery cycle performance test diagram in Example 4;

[0027] Figure 6 This is a full battery cycle performance test diagram in Example 5;

[0028] Figure 7 This is a full battery cycle performance test diagram in Example 6;

[0029] Figure 8 This is a graph showing the full battery cycle performance test in Example 7;

[0030] Fig. 9 This is a half-cell cycle performance test diagram in Example 8;

[0031] Fig.10 This is a half-cell cycle performance test diagram in Example 9;

[0032] Fig.11 This is a half-cell cycle performance test diagram in Example 10;

[0033] Fig.12 This is a half-cell cycle performance test diagram in Example 11;

[0034] Fig.13 This is a half-battery cycle performance test diagram in comparative example 1;

[0035] Fig.14 This is a half-battery cycle performance test diagram in comparative example 2;

[0036] Fig.15 This is a half-battery cycle performance test diagram in comparative example 3;

[0037] Fig.16 This is a full battery cycle performance test diagram in Comparative Example 4;

[0038] Fig.17 This is a full battery cycle performance test diagram in Comparative Example 5;

[0039] Fig.18 This is a full battery cycle performance test diagram in Comparative Example 6;

[0040] Fig.19 This is a full battery cycle performance test diagram in Comparative Example 7;

[0041] Fig. 20 This is a half-battery cycle performance test diagram in Comparative Example 8. DETAILED DESCRIPTION

[0042] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in the present invention are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.

[0044] In the present invention, unless otherwise specified, "first" and "second" do not indicate a sequence or limit to each material or step, but are only used to distinguish that they are not the same material or step. For example, "first" and "second" in "first solvent" and "second solvent" are only used to indicate that they are not the same solvent; similarly, "first" and "second" in "first electrolyte" and "second electrolyte" are only used to indicate that they are not the same electrolyte; "first" and "second" in "first contact" and "second contact" are only used to indicate that they are not the same contact.

[0045] A first aspect of the present invention provides a gel electrolyte, wherein the electrolyte comprises an electrolyte solution and a Nafion membrane modified by metal ions;

[0046] Wherein, the metal ion is selected from at least one of Group IA, Group IIA and Group IIIA elements;

[0047] Wherein, based on the total amount of the metal ion-modified Nafion membrane, the content of the metal ions is 0.1-5% by weight.

[0048] In the present invention, the content and type of metal ions are obtained by inductively coupled plasma (ICP) testing.

[0049] The present invention provides an ion bond-enhanced gel electrolyte, which utilizes the strong interaction between metal ions and sulfonic acid groups in Nafion to enhance the three-dimensional network structure of the Nafion membrane, uses an electrolyte to form a hydrophilic channel in the gel electrolyte, improves the ionic conductivity of the gel electrolyte, and can inhibit the dissolution and shuttling of organic electrode materials.

[0050] According to the present invention, preferably, the metal ion is selected from at least one of potassium ion, sodium ion, rubidium ion, barium ion, magnesium ion, calcium ion, aluminum ion, gallium ion, and indium ion, more preferably at least one of barium ion, aluminum ion, magnesium ion, and calcium ion, and further preferably barium ion. Under the above preferred embodiment, it is more conducive to improving the cycle stability and reversible capacity of the aqueous battery. The reason may be that the ionic bond interaction between the metal ions and the sulfonic acid groups on the Nafion skeleton causes them to cross-link, thereby enhancing the three-dimensional network structure of the Nafion membrane.

[0051] According to the present invention, preferably, the content of metal ions is 0.5-3% by weight based on the total amount of the metal ion-modified Nafion membrane.

[0052] The metal ion content in the present invention is within the above preferred range, which is more conducive to stabilizing the structure of the metal ion-modified Nafion diaphragm, more conducive to ion exchange and conduction, and improving the cycle stability and reversible capacity of the aqueous battery.

[0053] According to the present invention, preferably, the metal ion-modified Nafion membrane is swollen by an electrolyte.

[0054] According to the present invention, preferably, the average pore size of the metal ion-modified Nafion membrane is 0.01-1 μm, more preferably 0.05-0.5 μm.

[0055] In the present invention, the average pore size of the metal ion-modified Nafion membrane is obtained by scanning electron microscope (SEM) testing.

[0056] The average pore size of the metal ion-modified Nafion membrane in the present invention is within the above preferred range, which is more conducive to ion exchange and conduction, and improves the cycle stability and reversible capacity of the aqueous battery.

[0057] According to the present invention, preferably, the water contact angle of the metal ion-modified Nafion membrane is 80-90°, more preferably 84-88°.

[0058] In the present invention, the contact angle of the metal ion-modified Nafion membrane is obtained by static contact angle measurement using a contact angle meter and a water drop method (5 μL).

[0059] The contact angle of the metal ion-modified Nafion membrane of the present invention is within the above preferred range, which is more conducive to the infiltration of the electrolyte, prevents the leakage of the electrolyte, improves the interface stability, and improves the cycle stability and reversible capacity of the aqueous battery.

[0060] The present invention does not particularly limit the thickness of the metal ion-modified Nafion membrane, as long as it can meet the desired effect of the present invention. Those skilled in the art can select it according to actual needs. Preferably, the thickness of the metal ion-modified Nafion membrane is 10-100 μm, more preferably 20-50 μm.

[0061] According to the present invention, preferably, the solvent in the electrolyte is water.

[0062] According to the present invention, preferably, the solute in the electrolyte is selected from at least one of an acidic electrolyte, a neutral electrolyte and an alkaline electrolyte.

[0063] By selecting different aqueous electrolytes for swelling, the present invention successfully applies gel electrolytes to aqueous acidic, neutral and alkaline batteries, and successfully inhibits the shuttling behavior of various organic small molecules in aqueous batteries at different pH values, while improving the cycle and rate performance of aqueous batteries.

[0064] The acidic electrolyte in the present invention refers to an electrolyte having a pH value of less than 7 in aqueous solution.

[0065] In the present invention, a neutral electrolyte refers to a hydrogen ion (H + An electrolyte solution with equal concentrations of ions (OH-) and hydroxide ions (OH-) has a pH of approximately 7.

[0066] In the present invention, alkaline electrolyte refers to an electrolyte having a pH value greater than 7 in aqueous solution.

[0067] The present invention does not particularly limit the type of acidic electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario. Those skilled in the art can choose according to actual needs. Preferably, the acidic electrolyte is selected from at least one of H2SO4, HCl, H3PO4 and HClO4, more preferably H2SO4.

[0068] The present invention does not particularly limit the type of neutral electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario. Those skilled in the art can choose according to actual needs. Preferably, the neutral electrolyte is selected from at least one of ZnSO4, KCl, NaCl, LiCl, ZnCl2, Na2SO4, K2SO4, MnSO4 and Li2SO4, more preferably at least one of ZnSO4, ZnCl2 and MnSO4.

[0069] The present invention does not particularly limit the type of alkaline electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario, those skilled in the art can choose it according to actual needs. The alkaline electrolyte is selected from at least one of LiOH, NaOH and KOH, and more preferably KOH.

[0070] According to the present invention, preferably, the molar concentration of the solute in the electrolyte is 0.01-10 mol / L, more preferably 0.1-5 mol / L.

[0071] In the present invention, the molar concentration of the solute in the electrolyte is calculated based on the feed amount.

[0072] The molar concentration of the solute in the electrolyte of the present invention is within the above preferred range, which is more conducive to ion migration and conductivity improvement, and is more conducive to electrode reaction balance and improving the cycle stability and reversible capacity of the aqueous battery.

[0073] A second aspect of the present invention provides a method for preparing a gel electrolyte, wherein the method comprises the following steps:

[0074] (1) preparing a solution containing a first solvent and Nafion-H, and then performing a membrane forming process to obtain a Nafion-H membrane;

[0075] (2) in the presence of a second solvent, bringing the Nafion-H membrane into first contact with a metal precursor to obtain a metal ion-modified Nafion membrane;

[0076] Wherein, the metal in the metal precursor is selected from at least one of Group IA, Group IIA and Group IIIA elements;

[0077] The amount of Nafion-H membrane and metal precursor used is such that the metal ion content in the prepared metal ion-modified Nafion membrane is 0.1-5 wt %;

[0078] (3) in the presence of an organic solvent, the metal ion-modified Nafion membrane contacts the first electrolyte and swells;

[0079] (4) contacting the product obtained in step (3) with a second electrolyte to replace the organic solvent.

[0080] The present invention obtains a Nafion-H membrane by preparing a Nafion-H solution and performing a membrane forming treatment, thereby providing a stable skeleton support for subsequent operations, improving the ion conduction performance and enhancing the stability of the membrane through metal ion modification and electrolyte swelling, ensuring uniform ion distribution and rapid transmission, and improving the cycle stability and reversible capacity of the aqueous battery.

[0081] It should be noted that Nafion-H in the present invention refers to a perfluorosulfonic acid polymer, the structure of which is shown in Formula I and is well known to those skilled in the art.

[0082]

[0083] The present invention has no particular limitation on the source of the Nafion-H, which can be obtained commercially.

[0084] According to the present invention, preferably, the weight average molecular weight of the Nafion-H is 10,000-50,000.

[0085] According to the present invention, preferably, the method further comprises repeating step (3) and step (4).

[0086] The present invention has no particular limitation on the number of repetitions, as long as the metal ion-modified Nafion membrane can be fully swollen, and those skilled in the art can select the number according to actual needs.

[0087] In the present invention, "sufficient swelling" means that the Nafion-H membrane reaches a swelling equilibrium state after being swollen in the first solvent or the second solvent. At this time, the shape and size of the Nafion-H membrane remain stable, no significant solvent exchange process occurs in the membrane, and its shape, size and mass no longer change.

[0088] According to the present invention, preferably, in step (1), the usage ratio of Nafion-H to the first solvent is 1:5-13, more preferably 1:6-12.

[0089] The present invention does not particularly limit the type of the first solvent, as long as it can dissolve Nafion-H. Those skilled in the art can select it according to actual needs. Preferably, the first solvent is selected from at least one of ethanol, isopropanol, methanol, acetone and dimethyl sulfoxide, more preferably ethanol.

[0090] The present invention does not particularly limit the method of film-forming treatment, as long as the Nafion-H solution can be formed into a film. Those skilled in the art can choose according to actual needs. According to a specific embodiment of the present invention, the solution containing the first solvent and Nafion-H can be dropped into a PET culture dish and dried to obtain a Nafion-H membrane.

[0091] According to the present invention, preferably, the thickness of the Nafion-H membrane is 10-100 μm, more preferably 20-50 μm.

[0092] According to the present invention, preferably, the amount of Nafion-H membrane and metal precursor used is such that the content of metal ions in the prepared metal ion-modified Nafion membrane is 0.5-3% by weight.

[0093] According to the present invention, preferably, the metal precursor is selected from at least one of hydrochloride, nitrate and acetate of the metal, more preferably hydrochloride.

[0094] According to the present invention, preferably, the metal of the metal precursor is selected from at least one of barium, aluminum, magnesium and calcium, more preferably barium.

[0095] According to the present invention, preferably, the second solvent is water.

[0096] The present invention does not particularly limit the first contact method, as long as it is conducive to fully contacting the Nafion-H membrane with the metal precursor, and those skilled in the art can select it according to actual needs. According to some preferred embodiments of the present invention, the first contact method includes: immersing the Nafion-H membrane in a metal precursor solution, and washing it with deionized water after sufficient contact.

[0097] It should be noted that the present invention has no particular limitation on the washing agent and the amount thereof, and the washing can be carried out by conventional means in the art, for example, deionized water, as long as the excess metal ions on the surface of the metal ion-modified Nafion membrane can be removed by washing.

[0098] The present invention has no particular limitation on the time of the first contact, as long as it is conducive to sufficient contact between the Nafion-H membrane and the metal precursor. Those skilled in the art can select the time according to actual needs, for example, it can be 12-24 hours.

[0099] According to the present invention, preferably, the mass ratio of the metal ion-modified Nafion membrane, the organic solvent and the first electrolyte is 1:1000-10000:1000-10000, more preferably 1:2000-5000:2000-5000.

[0100] The present invention does not particularly limit the type of organic solvent, as long as it can swell the metal ion-modified Nafion membrane. Those skilled in the art can select it according to actual needs. Preferably, the organic solvent is selected from at least one of ethanol, isopropanol, methanol, acetone and dimethyl sulfoxide, more preferably ethanol.

[0101] In the present invention, the first solvent and the organic solvent may be the same or different.

[0102] The present invention does not particularly limit the contacting method in step (3), as long as the metal ion-modified Nafion membrane can be fully swollen, and those skilled in the art can select it according to actual needs. According to some preferred embodiments of the present invention, the contacting method includes: immersing the metal ion-modified Nafion membrane in a mixture of an organic solvent and a first electrolyte.

[0103] The present invention has no particular limitation on the contact time in step (3), as long as the metal ion-modified Nafion membrane can be fully swollen. Those skilled in the art can select the contact time according to actual needs, for example, 12-24 hours.

[0104] According to the present invention, preferably, the mass ratio of the substance obtained in step (3) to the second electrolyte is 1:1000-10000, more preferably 1:2000-5000.

[0105] The present invention does not particularly limit the second contacting method, as long as the organic solvent can be fully replaced, and those skilled in the art can select it according to actual needs. According to some preferred embodiments of the present invention, the second contacting method includes: immersing the product obtained in step (3) in a second electrolyte.

[0106] The present invention has no particular limitation on the time of the second contact, as long as the organic solvent can be fully replaced. Those skilled in the art can select the time according to actual needs, for example, it can be 12-24 hours.

[0107] According to the present invention, preferably, the solvent in the first electrolyte and the second electrolyte is each independently water.

[0108] According to the present invention, preferably, the solutes in the first electrolyte and the second electrolyte are each independently selected from at least one of an acidic electrolyte, a neutral electrolyte and an alkaline electrolyte.

[0109] It should be noted that, in the present invention, "independently" means that the first electrolyte and the second electrolyte can be the same or different, as long as the present invention can be implemented, and those skilled in the art can select according to actual needs. Preferably, the first electrolyte and the second electrolyte are the same.

[0110] By selecting different aqueous electrolytes for swelling, the present invention successfully applies gel electrolytes to aqueous acidic, neutral and alkaline batteries, and successfully inhibits the shuttling behavior of various organic small molecules in aqueous batteries at different pH values, while improving the cycle and rate performance of aqueous batteries.

[0111] The meanings of the acidic electrolyte, neutral electrolyte and alkaline electrolyte in the present invention are the same as those described above, and the present invention will not be repeated here.

[0112] The present invention does not particularly limit the type of acidic electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario. Those skilled in the art can choose according to actual needs. Preferably, the acidic electrolyte is selected from at least one of H2SO4, HCl, H3PO4 and HClO4, more preferably H2SO4.

[0113] The present invention does not particularly limit the type of neutral electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario. Those skilled in the art can choose according to actual needs. Preferably, the neutral electrolyte is selected from at least one of ZnSO4, KCl, NaCl, LiCl, ZnCl2, Na2SO4, K2SO4, MnSO4 and Li2SO4, more preferably at least one of ZnSO4, ZnCl2 and MnSO4.

[0114] The present invention does not particularly limit the type of alkaline electrolyte, as long as it can function normally in the corresponding electrochemical system or application scenario, those skilled in the art can choose it according to actual needs. The alkaline electrolyte is selected from at least one of LiOH, NaOH and KOH, and more preferably KOH.

[0115] According to the present invention, preferably, the molar concentration of the solute in the first electrolyte and the second electrolyte is independently 0.01-10 mol / L, more preferably 0.1-5 mol / L.

[0116] The third aspect of the present invention provides a gel electrolyte prepared by the method described in the second aspect.

[0117] The fourth aspect of the present invention provides use of the gel electrolyte described in the first aspect and the third aspect in a battery.

[0118] According to the present invention, preferably, the gel electrolyte is used as a separator in a battery.

[0119] The specific methods of the application of the gel electrolyte in the battery and the preparation method of the working electrode of the present invention are well known to those skilled in the art and are not particularly limited. For example, a metal ion-modified Nafion diaphragm can be used for battery assembly.

[0120] The present invention has no particular limitation on the type of battery. For example, the battery may be button-type, soft-pack, cylindrical, or square. According to a specific embodiment of the present invention, the button-type is preferred.

[0121] The present invention has no particular restrictions on other components of the battery except the separator, and can be applied to various positive and negative electrodes under different pH environments. For example, the positive electrode can be selected from iodine, nickel hydroxide and hexaazatrinaphthalene tricarbonitrile (3CN-DQPZ); the negative electrode sheet can be selected from zinc sheet and hexaazatrinaphthalene tricarbonitrile (3CN-DQPZ).

[0122] The positive electrode and / or negative electrode may also contain conductive agents and other conventional additives in the art, and the present invention has no particular limitation on this, and those skilled in the art may select the additives according to actual needs.

[0123] The present invention will be described in detail below through examples.

[0124] In the following examples and comparative examples, unless otherwise specified, conventional methods are used; the reagents and materials used, unless otherwise specified, are commercially available and / or prepared by methods known in the art.

[0125] In the following examples and comparative examples, unless otherwise specified, hexaazatrinaphthalene tricarbonitrile (3CN-DQPZ) was used as the positive electrode;

[0126] In the following examples and comparative examples, the weight average molecular weight of Nafion-H is 30,000.

[0127] In the following comparative examples and embodiments, the methods for characterizing the content and type of metal ions, the average pore size of the metal ion-modified Nafion membrane, and the contact angle of the metal ion-modified Nafion membrane are as described above and will not be repeated here.

[0128] In the following comparative examples and examples, efficiency = discharge specific capacity / charge specific capacity × 100%.

[0129] Example 1

[0130] (1) Weigh 10 g of Nafion-H powder and dissolve it in 90 g of ethanol. Stir for 12 h to obtain a uniform Nafion ethanol solution. Then take 5 g of the above Nafion ethanol solution and drop it into a PET culture dish with a diameter of 60 mm until the solution evenly covers the bottom of the culture dish. Place it in a 60°C forced air drying oven and dry it for 10 hours to obtain a uniform Nafion-H membrane with a thickness of 30 μm.

[0131] (2) The Nafion membrane was immersed in a 1 mol / L BaCl2 aqueous solution for 12 h and then the excess Ba on the surface of the Nafion membrane was washed away with deionized water. 2+ , obtain Nafion-Ba 2+ membrane.

[0132] (3) The above Nafion-Ba 2+ The membrane was immersed in a mixed solution of ethanol and 2 mol / L H2SO4 for 12 h to fully swell it (the mass ratio of the metal ion-modified Nafion membrane, the organic solvent and the first electrolyte was 1:5000:5000).

[0133] (4) The product obtained in step (3) was transferred into 2 mol / L H2SO4 for 12 h to fully replace the ethanol molecules (the mass ratio of the substance obtained in step (3) to the second electrolyte was 1:5000), and the above swelling and replacement process was repeated many times until the Nafion membrane was filled with electrolyte to obtain acidic Nafion-Ba 2+ Hydrogel electrolyte. The parameters of metal ion modified Nafion membrane are shown in Table 1. Acidic Nafion-Ba 2+ The appearance of hydrogel electrolyte is Figure 1 shown.

[0134] The hydrogel electrolyte was punched into discs with a diameter of 13 mm for battery assembly.

[0135] Prepare a mass ratio of 6:3:1 between hexaazatrinaphthalene tricarbonitrile (3CN-DQPZ), Ketjen black and polyvinylidene fluoride (PVDF). First, mix 3CN-DQPZ and Ketjen black and grind them evenly. Dissolve PVDF in an appropriate amount of N-methylpyrrolidone (NMP) and then add the ground mixture of 3CN-DQPZ and Ketjen black. Grind them evenly to obtain 3CN-DQPZ slurry. Apply the above slurry onto a carbon paper with a diameter of 12 mm and place it in a vacuum drying oven to dry for 8 hours to obtain a 3CN-DQPZ electrode sheet. The 3CN-DQPZ content of the electrode sheet is about 1.5 mg / cm 2The 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 1, and the activated carbon counter electrode were assembled in a Swagelok battery case and left to stand for 1 hour before the electrochemical performance test. Figure 1 As shown, at a current density of 1A g -1 Under the conditions, the first discharge capacity of the half-cell is 248.5 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 248.8 mA h g -1 , the capacity retention rate is 100%. Half-battery cycle performance test Figure 2 shown.

[0136] Example 2

[0137] The method of Example 1 is followed, except that the 2 mol / L H2SO4 in step (3) and step (4) is replaced by an equal amount of 2 mol / L ZnSO4. The parameters of the metal ion-modified Nafion membrane are shown in Table 1.

[0138] The method of Example 1 was followed, except that the 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 2, and the activated carbon counter electrode were assembled in a Swagelok battery case and the electrochemical performance was tested after standing for 1 hour. At a current density of 1A g-1, the maximum discharge capacity of the half-cell was 221.8 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 221.5 mA h g -1 , the capacity retention rate is 99.8%. Half-battery cycle performance test Figure 3 shown.

[0139] Example 3

[0140] The method of Example 1 is followed, except that the 2 mol / L H2SO4 in step (3) and step (4) is replaced by an equal amount of 2 mol / L KOH. The parameters of the metal ion-modified Nafion membrane are shown in Table 1.

[0141] The method of Example 1 was followed, except that the 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 3, and the activated carbon counter electrode were assembled in a Swagelok battery case and the electrochemical performance was tested after standing for 1 hour. -1 Under these conditions, the maximum discharge capacity of the half-cell is 216.1 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 211mA hg -1 The capacity retention rate is 97.6%. The parameters of the metal ion modified Nafion membrane are shown in Table 1. The half-battery cycle performance test is as follows Figure 4 shown.

[0142] Example 4

[0143] The method of Example 1 is followed, except that the 2 mol / L H2SO4 in step (3) and step (4) is replaced by an equal volume of 2 mol / L H2SO4 + 1 mol / L MnSO4. The parameters of the metal ion-modified Nafion membrane are shown in Table 1.

[0144] The method of Example 1 was followed, except that the 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 4, and the carbon felt counter electrode were assembled in a Swagelok battery case and the electrochemical performance was tested after standing for 1 hour. -1 Under the conditions, the first discharge capacity of the full battery is 227.3mA hg -1 , and the reversible discharge capacity after 1000 cycles is 219mA hg -1 The capacity retention rate is 96.3%. The parameters of the metal ion modified Nafion membrane are shown in Table 1. The full battery cycle performance test is as follows Figure 5 shown.

[0145] Example 5

[0146] The method of Example 2 was followed, except that the 3CN-DQPZ electrode sheet (positive electrode), the gel electrolyte prepared in Example 2, and the zinc sheet negative electrode were assembled in a Swagelok battery case and the electrochemical performance was tested after standing for 1 hour. -1 Under the conditions, the first discharge capacity of the full battery is 218.3mA hg -1 , and the reversible discharge capacity after 1000 cycles is 209.2 mA h g -1 The capacity retention rate is 95.8%. The parameters of the metal ion modified Nafion membrane are shown in Table 1. The full battery cycle performance test is as follows Figure 6 shown.

[0147] Example 6

[0148] The method of Example 3 is followed, except that the 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 3, and the nickel hydroxide positive electrode are assembled in a Swagelok battery case, and the electrochemical performance is tested after standing for 1 hour. Among them, the preparation method of the nickel hydroxide positive electrode is: nickel hydroxide powder is mixed with nickel powder (conductive additive) and polyvinylidene fluoride (binder) in a mass ratio of 6:3:1, and then an appropriate amount of NMP is added and fully ground to obtain a slurry of nickel hydroxide electrode. The slurry is evenly coated on a nickel foam with a diameter of 16 mm, and a nickel hydroxide electrode sheet is obtained after vacuum drying. At a current density of 1A g -1Under these conditions, the maximum discharge capacity of the full battery is 213.3 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 194.7 mAh g -1 The capacity retention rate is 91.3%. The parameters of the metal ion modified Nafion membrane are shown in Table 1. The full battery cycle performance test is as follows Figure 7 shown.

[0149] Example 7

[0150] The method of Example 1 is followed, except that the 2 mol / L H2SO4 in step (3) and step (4) is replaced by an equal volume of 2 mol / L ZnSO4 + 0.5 mol / L ZnCl2. The parameters of the metal ion-modified Nafion membrane are shown in Table 1.

[0151] The method of Example 1 is followed, except that the gel electrolyte, zinc sheet negative electrode and iodine positive electrode prepared in Example 7 are assembled in a Swagelok battery case, and the electrochemical performance is tested after standing for 1 hour. Among them, the preparation method of the iodine positive electrode is: 0.5g iodine and 0.5g activated carbon (AC) are fully mixed by grinding. The mixed powder is then placed in a hydrothermal reactor, heated at 100°C for 12 hours, and cooled to obtain a porous carbon-coated iodine (iodine @ AC) composite electrode material. After mixing the iodine composite electrode material with Ketjen black (conductive additive) and polyvinylidene fluoride (binder) in a mass ratio of 8:1:1, an appropriate amount of NMP is added and fully ground to obtain an iodine electrode slurry. The slurry is evenly coated on carbon paper with a diameter of 12 mm, and an iodine electrode pole piece is obtained after vacuum drying, with an iodine loading of 1.5-2.5 mg. At a current density of 1A g -1 Under the conditions, the first discharge capacity of the full battery is 258.7mA hg -1 , and the reversible discharge capacity after 500 cycles is 181.5 mA h g -1 The capacity retention rate is 70.2%. The full battery cycle performance test is as follows Figure 8 shown.

[0152] Example 8

[0153] (1) Weigh 10g of Nafion-H powder and dissolve it in 120g of ethanol. Stir for 24h to obtain a uniform Nafion ethanol solution. Then take 5g of the above Nafion ethanol solution and drop it into a PET culture dish with a diameter of 60mm until the solution evenly covers the bottom of the culture dish. Place it in a 60℃ forced air drying oven and dry it for 10 hours to obtain a uniform Nafion-H membrane with a thickness of 35μm.

[0154] (2) The Nafion membrane was immersed in a 0.1 mol / L BaCl2 aqueous solution for 24 h and then the excess Ba on the surface of the Nafion membrane was washed away with deionized water. 2+ , obtain Nafion-Ba 2+ membrane.

[0155] (3) The above Nafion-Ba 2+ The membrane was immersed in a mixed solution of ethanol and 5 mol / L H2SO4 for 24 h to fully swell it (the mass ratio of the metal ion-modified Nafion membrane, the organic solvent and the first electrolyte was 1:2000:2000).

[0156] (4) The product obtained in step (3) was transferred into 5 mol / L H2SO4 for 12 h to fully replace the ethanol molecules (the mass ratio of the substance obtained in step (3) to the second electrolyte was 1:2000), and the above swelling and replacement process was repeated many times until the Nafion membrane was filled with electrolyte to obtain acidic Nafion-Ba 2+ Hydrogel electrolyte. The parameters of metal ion-modified Nafion membrane are shown in Table 1.

[0157] The above hydrogel electrolyte was punched into a disc with a diameter of 13 mm for battery assembly. Prepare a mass ratio of 6:3:1 between hexaazatrinaphthalene tricarbonitrile (3CN-DQPZ), Ketjen black and polyvinylidene fluoride (PVDF). First, 3CN-DQPZ and Ketjen black were mixed and ground evenly. PVDF was dissolved in an appropriate amount of N-methylpyrrolidone (NMP) and then the ground mixture of 3CN-DQPZ and Ketjen black was added. The mixture was fully ground to obtain 3CN-DQPZ slurry. The above slurry was scraped onto a carbon paper with a diameter of 12 mm and placed in a vacuum drying oven for 8 hours to obtain a 3CN-DQPZ electrode sheet. The 3CN-DQPZ content of the electrode sheet was about 1.5 mg / cm 2 The 3CN-DQPZ electrode sheet, the gel electrolyte prepared in Example 1, and the activated carbon counter electrode were assembled in a Swagelok battery case and left to stand for 1 hour before the electrochemical performance test. Fig. 9 As shown, at a current density of 1A g -1 Under the conditions, the first discharge capacity of the half-cell is 248.6 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 228mA hg -1 The capacity retention rate is 91.7%. The half-battery cycle performance test is as follows Fig. 9 shown.

[0158] Example 9

[0159] The method of Example 1 was followed, except that the Nafion membrane was immersed in a 1.5 mol / L BaCl2 aqueous solution. The parameters of the metal ion-modified Nafion membrane are shown in Table 1. -1 Under the conditions, the first discharge capacity of the half-cell is 237.9 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 230.1 mA h g -1 The capacity retention rate is 96.7%. The half-battery cycle performance test is as follows Fig.10 shown.

[0160] Example 10

[0161] The method of Example 1 was followed, except that the Nafion membrane was immersed in a 0.05 mol / L BaCl2 aqueous solution. The parameters of the metal ion-modified Nafion membrane are shown in Table 1. -1 Under the conditions, the first discharge capacity of the half-cell is 233.1 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 214.7 mA h g -1 The capacity retention rate is 92.1%. The half-battery cycle performance test is as follows Fig.11 shown.

[0162] Embodiment 11

[0163] The method of Example 1 was followed, except that the Nafion membrane was immersed in a 1 mol / L AlCl3 aqueous solution. The parameters of the metal ion-modified Nafion membrane are shown in Table 1. -1 Under the conditions, the first discharge capacity of the half-cell is 223 mAh g -1 , and the reversible discharge capacity after 500 cycles is 199.1 mA h g -1 The capacity retention rate is 89.3%. The half-battery cycle performance test is as follows Fig.12 shown.

[0164] Comparative Example 1

[0165] The method of Example 1 was followed, except that a commercial glass fiber separator (a commercial product with the specification of GF / A from Whatman Company) was directly used as the separator in the assembled battery, and the electrolyte was 2 mol / L H2SO4. -1 Under the conditions, the first discharge capacity of the half-cell is 230mA hg -1 , and the reversible discharge capacity after 1000 cycles is 197.9 mA h g -1 The capacity retention rate is 86%. The half-battery cycle performance test is as follows Fig.13 shown.

[0166] Comparative Example 2

[0167] The method of Example 1 was followed, except that the glass fiber diaphragm was used directly as the diaphragm in the assembled battery, and 2 mol / L ZnSO4 was used as the electrolyte. -1 Under the conditions, the first discharge capacity of the half-cell is 200.7 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 177.2 mA h g -1 The capacity retention rate is 88.3%. The half-battery cycle performance test is as follows Fig.14 shown.

[0168] Comparative Example 3

[0169] The method of Example 1 was followed, except that the glass fiber diaphragm was used directly as the diaphragm in the assembled battery, and 2 mol / L KOH was used as the electrolyte. -1 Under the conditions, the first discharge capacity of the half-cell is 227 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 134.8 mA h g -1 The capacity retention rate is 59.4%. The half-battery cycle performance test is as follows Fig.15 shown.

[0170] Comparative Example 4

[0171] The method of Example 4 was followed, except that the glass fiber diaphragm was used directly as the diaphragm in the assembled battery, and 2M H2SO4+1M MnSO4 was used as the electrolyte. -1 Under the conditions, the first discharge capacity of the half-cell is 203.5 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 175.6 mA h g -1 The capacity retention rate is 86.3%. The full battery cycle performance test is as follows Fig.16 shown.

[0172] Comparative Example 5

[0173] The method of Example 5 was followed, except that the glass fiber diaphragm was used directly as the diaphragm in the assembled battery, and 2 mol / L ZnSO4 was used as the electrolyte. -1 Under the conditions, the first discharge capacity of the half-cell is 198.5 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 188.6 mA h g -1 , the capacity retention rate is 95%. Full battery cycle performance test Fig.17 shown.

[0174] Comparative Example 6

[0175] The method of Example 6 was followed, except that the glass fiber diaphragm was used directly as the diaphragm in the assembled battery, and 2 mol / L KOH was used as the electrolyte. -1 Under the above conditions, the first discharge capacity of the half-cell is 193.8 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 168.1 mA h g -1 The capacity retention rate is 86.7%. The full battery cycle performance test is as follows Fig.18 shown.

[0176] Comparative Example 7

[0177] The method of Example 7 was followed, except that the glass fiber separator was used directly as the separator in the assembled battery, and 2 mol / L ZnSO4 + 0.5 mol / L ZnCl2 was used as the electrolyte. -1 Under the conditions, the first discharge capacity of the half-cell is 190.6 mA hg -1 , and the reversible discharge capacity after 500 cycles is 128.1 mA h g -1 The capacity retention rate is 67.2%. The full battery cycle performance test is as follows Fig.19 shown.

[0178] Comparative Example 8

[0179] The method of Example 1 was followed, except that the Nafion membrane was immersed in a 0.01 mol / L BaCl2 aqueous solution. The parameters of the metal ion-modified Nafion membrane are shown in Table 1. -1 Under the conditions, the first discharge capacity of the half-cell is 240.3 mA hg -1 , and the reversible discharge capacity after 1000 cycles is 197.4 mA h g -1 The capacity retention rate is 85.7%. The half-battery cycle performance test is as follows Fig. 20 shown.

[0180] Table 1

[0181]

[0182] It can be seen from the above results that the present invention provides an ion-enhanced Nafion-based hydrogel electrolyte, and applies it to aqueous acidic, neutral, and alkaline batteries to improve the electrochemical performance of aqueous batteries. During the preparation process, the three-dimensional network structure of the Nafion membrane is enhanced by the strong interaction between metal ions and sulfonic acid groups, and then the gel network is gradually swollen using aqueous electrolytes to form hydrophilic channels, which greatly improves the ionic conductivity of the Nafion hydrogel electrolyte. Compared with the comparative example, by selecting different aqueous electrolytes for swelling, the Nafion hydrogel electrolyte is successfully applied to aqueous acidic, neutral, and alkaline batteries, successfully inhibiting the shuttling behavior of various organic small molecules in aqueous batteries at different pH values, while improving the circulation and reversible capacity of aqueous batteries.

[0183] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A gel electrolyte, characterized in that: The electrolyte includes an electrolyte solution and a Nafion diaphragm modified by metal ions; Wherein, the metal ion is selected from at least one of Group IA, Group IIA and Group IIIA elements; Wherein, based on the total amount of the metal ion-modified Nafion membrane, the content of the metal ions is 0.1-5% by weight.

2. The electrolyte according to claim 1, wherein The metal ion is selected from at least one of barium ion, aluminum ion, magnesium ion and calcium ion, preferably barium ion; and / or, based on the total amount of the metal ion-modified Nafion membrane, the content of the metal ion is 0.5-3 wt %; And / or, the metal ion-modified Nafion membrane is swollen by the electrolyte.

3. The electrolyte according to claim 1 or 2, wherein The average pore size of the metal ion-modified Nafion membrane is 0.01-1 μm, preferably 0.05-0.5 μm; and / or, the water contact angle of the metal ion-modified Nafion membrane is 80-90°, preferably 84-88°; And / or, the thickness of the metal ion-modified Nafion membrane is 10-100 μm, preferably 20-50 μm.

4. The electrolyte according to any one of claims 1 to 3, wherein The solute in the electrolyte is selected from at least one of an acidic electrolyte, a neutral electrolyte and an alkaline electrolyte; Preferably, the acidic electrolyte is selected from at least one of H2SO4, HCl, H3PO4 and HClO4, preferably H2SO4; Preferably, the neutral electrolyte is selected from at least one of ZnSO4, KCl, NaCl, LiCl, ZnCl2, Na2SO4, K2SO4, MnSO4 and Li2SO4, preferably at least one of ZnSO4, ZnCl2 and MnSO4; Preferably, the alkaline electrolyte is selected from at least one of LiOH, NaOH and KOH, preferably KOH; And / or, the solvent in the electrolyte is water; Preferably, the molar concentration of the solute in the electrolyte is 0.01-10 mol / L, preferably 0.1-5 mol / L.

5. A method for preparing a gel electrolyte, characterized in that: The method comprises the following steps: (1) preparing a solution containing a first solvent and Nafion-H, and then performing a membrane forming process to obtain a Nafion-H membrane; (2) in the presence of a second solvent, bringing the Nafion-H membrane into first contact with a metal precursor to obtain a metal ion-modified Nafion membrane; Wherein, the metal in the metal precursor is selected from at least one of Group IA, Group IIA and Group IIIA elements; The amount of Nafion-H membrane and metal precursor used is such that the metal ion content in the prepared metal ion-modified Nafion membrane is 0.1-5 wt %; (3) in the presence of an organic solvent, the metal ion-modified Nafion membrane contacts the first electrolyte and swells; (4) contacting the product obtained in step (3) with a second electrolyte to replace the organic solvent.

6. The method according to claim 5, wherein: The method further comprises repeating step (3) and step (4); And / or, in step (1), the ratio of Nafion-H to the first solvent is 1:5-13; and / or, the first solvent is selected from at least one of ethanol, isopropanol, methanol, acetone and dimethyl sulfoxide, preferably ethanol; and / or, the thickness of the Nafion-H membrane is 10-100 μm, preferably 20-50 μm; And / or, the weight average molecular weight of the Nafion-H is 10000-50000.

7. The method according to claim 5 or 6, wherein: The amount of Nafion-H membrane and metal precursor is such that the metal ion content in the prepared metal ion-modified Nafion membrane is 0.5-3 wt %; and / or, the metal precursor is selected from at least one of a hydrochloride, a nitrate and an acetate of a metal, preferably a hydrochloride; And / or, the second solvent is water.

8. The method according to any one of claims 5 to 7, wherein: The mass ratio of the metal ion-modified Nafion membrane, the organic solvent and the first electrolyte is 1:1000-10000:1000-10000; And / or, the organic solvent is selected from at least one of ethanol, isopropanol, methanol, acetone and dimethyl sulfoxide, preferably ethanol.

9. The method according to any one of claims 5 to 8, wherein: The mass ratio of the substance obtained in step (3) to the second electrolyte is 1:1000-10000; and / or, the solutes in the first electrolyte and the second electrolyte are each independently selected from at least one of an acidic electrolyte, a neutral electrolyte and an alkaline electrolyte; Preferably, the acidic electrolyte is selected from at least one of H2SO4, HCl, H3PO4 and HClO4, preferably H2SO4; Preferably, the neutral electrolyte is selected from at least one of ZnSO4, KCl, NaCl, LiCl, ZnCl2, Na2SO4, K2SO4, MnSO4 and Li2SO4, preferably at least one of ZnSO4, ZnCl2 and MnSO4; Preferably, the alkaline electrolyte is selected from at least one of LiOH, NaOH and KOH, preferably KOH; And / or, the solvent in the first electrolyte and the second electrolyte is independently water; Preferably, the molar concentration of the solute in the first electrolyte and the second electrolyte is independently 0.01-10 mol / L, preferably 0.1-5 mol / L.

10. A gel electrolyte prepared by the method according to any one of claims 5 to 9.

11. Use of the gel electrolyte according to any one of claims 1 to 4 and 10 in a battery.